(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Improving the quality of education and aligning the teaching process with contemporary demands have become urgent priorities. This article explores the pedagogical system for enhancing the reinforcement method within blended learning. The process of refining reinforcement methods is presented as a complex and multidimensional approach aimed at increasing student motivation. By integrating various motivational strategies into the blended learning environment, this pedagogical system fosters active participation, cognitive engagement, and independent learning. The article also highlights the practical application of blended instruction through digital tools, classroom activities, and gamified incentives designed to boost students’ academic performance and motivation.